The impact of cocaine on adult hippocampal neurogenesis: Potential neurobiological mechanisms and contributions to maladaptive cognition in cocaine addiction disorder - Castilla-Ortega, María Estela; Ladrón de Guevara-Miranda, David; Serrano, Antonia; Pavón, Francisco Javier; Suárez, Juan; Rodriguez-de-Fonseca, Fernando; Santín-Núñez, Luis Javier (Elsevier, 2017)
After discovering that addictive drugs alter adult neurogenesis, the potential role of adult-born hippocampal neurons in drug addiction has become a promising research field, in which cocaine is the most frequently investigated drug. Although a substantial amount of pre-clinical evidence has accumulated, additional studies are required to reveal the mechanisms by which cocaine modulates adult hippocampal neurogenesis (AHN) and determine whether these adult-born neurons have a role in cocaine-related behaviors, such as cocaine-mediated cognitive symptoms. First, this review will summarize the cocaine-induced alterations in a number of neurobiological factors (neurotransmitters, neurotrophins, glucocorticoids, inflammatory mediators) that likely regulate both hippocampal-dependent learning and adult hippocampal neurogenesis after cocaine exposure. A separate section will provide a detailed review of the available literature that challenges the common view that cocaine reduces adult hippocampal neurogenesis. In fact, cocaine has a short-term anti-proliferative role, but the young adult-born neurons are apparently spared, or even enhanced, following certain cocaine protocols. Thus, we will try to reconcile this evidence with the hippocampal-dependent cognitive symptoms that are typically observed in cocaine addicts, and we will propose new directions for future studies to test the relevant hypothesis. Based on the evidence presented here, the regulation of adult hippocampal neurogenesis might be one of the many mechanisms by which cocaine sculpts hippocampus-dependent learning.
Keywords: Cocaína; Vulnerability; Associative memory; Conditioned place preference; Withdrawal; Relapse